Experiences and concerns of pregnant refugee women from Nigeria seeking for asylum in Germany - a qualitative analysis - Lindermaier, Nina; Rzepka-Marot, Irja; Zehetmair, Catharina; Kaufmann, Claudia; Friederich, Hans-Christoph; Nikendei, Christoph (Midwifery, 2025)
Problem - Insights into and data of the experiences of pregnant women seeking asylum in Germany are largely lacking. - Background - Due to multiple stress factors, pregnant refugees are considered a vulnerable group. Gender-specific causes of flight, traumatic experiences during flight, and numerous stressors in the respective host country have a decisive impact on the health of women and affect pregnancy and childbirth. - Aim - This study aims to assess the perspectives and needs of pregnant refugee women from Nigeria, that are residing in an initial reception center in Germany. - Methods - Experiences and concerns of N = 20 pregnant refugee women from Nigeria relating to pregnancy and impending childbirth were assessed in semi-structured interviews, conducted by three psychologists in English. - Findings - Findings emphasize the need for continuous medical and psychotherapeutic care due to the multiple stressors and the partial lack of social support, especially for single women. The participants described their concerns particularly related to their personal and their family's health, as well as their impending birth, their optimistic attitude about the parenting experience, and confidence in medical care in Germany. Their wishes were predominantly related to items necessary for the care of their children, information about the pregnancy and birth process as well as for their integration. Utilization of resources and positive activities were indicative of adapting coping styles and resilience factors of pregnant refugee women. - Conclusion - This study highlights the importance of the context-sensitive medical and psychotherapeutic care to adequately support the women during pregnancy and around childbirth. Furthermore, the study demonstrates the necessity of counteracting the negative effects of experiences on their health and that of their children.